Report of the 7th international workshop on colposcopy, screening and prevention of cervical cancer, Douala, Cameroon, March 30 - 31 and April 1st 2016 - Fouogue, Jovanny Tsuala; Sando, Zacharie; Fouelifack, Florent Ymele; Fouedjio, Jeanne Hortence; Tebeu, Pierre Marie; Kamgaing, Jacques Tsingaing; Vassilakos, Pierre; Petignat, Patrick (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Authors herein report the proceedings of the 7th international workshop on colposcopy, screening and prevention of cervical cancer held in Douala (Cameroon) on March 30 - 31 and April 1, 2016. Methods: As with previous conferences of this series, the 2016 edition provided an excellent forum for exchange of information and opinions between the researchers, clinicians, laboratory scientists and regulatory bodies. It also stood as an opportunity for further training of health staff on prevention and screening of cervical cancer. Results: The workshop covered both accepted and emerging methods of preventing and screening cervical cancer with emphasis on current clinical and public health practice in low and middle-income countries. The topic was covered by complementary sessions: cervical principles, cervical cancer epidemiology and prevention strategy; cervical cancer management and treatment; cervical cancer screening programs in Cameroon; innovations in cervical cancer screening and perspectives in cervical cancer screening. This report also summarizes the presentations done during the workshop. This 7th edition set up the record of attendance with more than 150 participants of several backgrounds (specialist physicians and nurses, laboratory technicians, socio-anthropologists, university lecturers and managers of health systems) from more than 19 local and international institutions. Conclusions: Master’s classes, free communications and discussions were fruitful and appointment was taken for March 30-31, 2017 in Yaounde (Cameroon).